PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA: PENGARUH CAR, NPF, FDR, INFLASI, DAN BI RATE - Laela, Nur; Indriyani, Rinni; Sari, Fitriya (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
SThis study aims to analyze and measure the impact of Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), Inflation, and BI Rate on the profitability of Islamic Commercial Banks (BUS) in Indonesia. This study adopts a quantitative approach, using panel data which is then processed through multiple linear regression. Partially, the main findings indicate that NPF significantly affects profitability negatively, while FDR has a significant positive correlation. Meanwhile, the CAR, Inflation, and BI Rate variables were found to have no significant effect. The result of this research are expected to enrich the Islamic finance literature and provide practical input for banking management in making strategic decisions to achieve optimal and sustainable financial performance.